Experience-Dependent Regulation of Cajal–Retzius Cell Networks in the Developing and Adult Mouse Hippocampus. (16th June 2017) - Anstötz, Max; Lee, Sun Kyong; Neblett, Tamra I; Rune, Gabriele M; Maccaferri, Gianmaria
Abstract: In contrast to their near-disappearance in the adult neocortex, Cajal–Retzius cells have been suggested to persist longer in the hippocampus. A distinctive feature of the mature hippocampus, not maintained by other cortical areas, is its ability to sustain adult neurogenesis. Here, we have investigated whether environmental manipulations affecting hippocampal postnatal neurogenesis have a parallel impact on Cajal–Retzius cells. We used multiple mouse reporter lines to unequivocally identify Cajal–Retzius cells and quantify their densities during postnatal development. We found that exposure to an enriched environment increased the persistence of Cajal–Retzius cells in the hippocampus, but not in adjacent cortical regions. We did not observe a similar effect for parvalbumin-expressing interneurons, which suggested the occurrence of a cell type-specific process. In addition, we did not detect obvious changes either in Cajal–Retzius cell electrophysiological or morphological features, when compared with what previously reported in animals not exposed to enriched conditions. However, optogenetically triggered synaptic output of Cajal–Retzius cells onto local interneurons was enhanced, consistent with our observation of higher Cajal–Retzius cell densities. In conclusion, our data reveal a novel form of hippocampal, cell type-specific, experience-dependent network plasticity. We propose that this phenomenon may be involved in the regulation of enrichment-dependent enhanced hippocampal postnatal neurogenesis.